Thermal controls for NTU student satellite series-I (SCOOB-I) satellite - Birthi, Sanika (Nanyang Technological University, 2020)
The development of miniature satellites for academic and scientific research is well understood due to its feasibility, cheaper manufacturing and launch costs, and capability of performing most tasks similar to larger ones. The satellites are subjected to harsh thermal load variations in orbit, affecting the performance of subsystems and payloads. Each component has a specified upper and lower operational temperature limit within which the thermal variations experienced in the orbit should reside. This dissertation primarily focusses on the thermal controls for the first satellite in NTU’s newly launched student satellite series: SCOOB-I. A detailed finite-difference thermal model for the 3U CubeSat in the equatorial orbit is simulated for expected launch times and mission operation. Thermal analyses for worst-case hot and worst-case cold conditions are conducted using a thermal engineering tool suite called C & R Thermal Desktop. The analysis results significantly influenced the thermal control strategies employed. Passive thermal control in the form of multi-layer insulation was adopted for the imager which previously reached unacceptable cold temperatures. The SCOOB-I satellite component temperatures were successfully maintained within their required limits after adopting thermal control. This study is then extended to conduct preliminary thermal modelling and analysis of a microsatellite named ARCADE: Atmospheric Coupling and Dynamic Explorer, which is going to be launched along with SCOOB-I. The preliminary findings showed that the components CIP_PCB and cold finger display overheating. Thus, thermal control would be necessary to keep the temperatures within the acceptable range.